Differences in Nobel laureates across disciplines - Lim, Davina Hui Hui (2014)
Are Economists really different from non-Economists? In this paper, we constructed a data set on Nobel Laureates’ personal life, to investigate if Economists are indeed different by studying their degree of self-interest across disciplines. Our study has made use of the observable characteristics of the Laureates such as the total number of children, year of award, affiliation at time of award, place of birth, scientific age, collaboration between the Laureate and spouse(s) and the number of times spouse(s) mentioned in the Official Biography of the Laureate, which may possibly affect the Laureates’ divorce rates and the acknowledgment of their spouse(s). Our main findings suggest that the total number of children plays an important role in influencing the Laureates’ divorce rates. Contrary to our expectations, Economists are not any more self-interested than Chemists and Physicists in terms of the divorce rates and sharing of credit with their spouse(s).